Landfill leachate treatment in Malaysia: Continuous circulation motion using mixed agricultural wastes with an open grid-like Luffa's configuration - Wae AbdulKadir W.A.F.; Che Omar R.; Roslan R.; Baharuddin I.N.Z. (Elsevier Ltd, 2024)
In this study, adsorbent materials from agriculture waste such as luffa, coconut husk, pineapple leaf and activated charcoal (AC) from coconut shell were synthesized and characterized. The material is termed as COLUFNAS/AC. The adsorbent material then was used to treat landfill leachate with ammonia as Total Kjeldahl Nitrogen (TKN), ammoniacal nitrogen (NH3?N), total suspended solid (TSS), turbidity, biochemical oxygen demand @5 days (BOD5), chemical oxygen demand (COD) and heavy metals with values of 2,279.2 ADMI, 417.2 mg/L, 1,0220 mg/L, 2,388 mg/L, 9,092 mg/L, 45,164 mg/L and <0.08 mg/L, respectively. The experiments were conducted at the laboratory and pilot scale. For laboratory scale, 8 PVC pipes with COLUFNAS/AC were used to treat 30 L of landfill leachate. Under 6 h operating conditions, COLUFNAS/AC was significantly reduced the TKN (44.84 %), turbidity (45.90 %), and COD (31.88 %). Therefore, the potential removal efficiency of COLUFNAS/AC at laboratory scale was further applied at pilot scale in pH adjustment and coagulation tanks for 15 days. The complex composition of leachate at pilot scale (30,605.5 m3) significantly improved the leachate quality by 11.11 %, 17.03 %, 12.92 %, 52.25 % and 55 % reduction of NH3N, TSS, turbidity, BOD5 and COD. The pH of leachate was also changed to less acidic. Implementing COLUFNAS/AC in both tanks not only effectively saved treatment costs to 3,955.22 USD/month but also achieved the lowest operational treatment cost at just 0.22 USD/m3. 2023 Elsevier Ltd